Association of plasma phospholipid long-chain ω-3 fatty acids with incident atrial fibrillation in older adults: the cardiovascular health study. - Wu, Jason H Y; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Sacks, Frank M; Rimm, Eric B; Heckbert, Susan R; Siscovick, David S; Mozaffarian, Dariush (Circulation, 2012)
BACKGROUND: Experimental studies suggest that long-chain n-3 polyunsaturated fatty acids (n-3 PUFAs) may reduce the risk of atrial fibrillation (AF). Prior studies evaluating fish or n-3 PUFA consumption from dietary questionnaires and incident AF have been conflicting. Circulating levels of n-3 PUFAs provide an objective measurement of exposure. METHODS AND RESULTS: Among 3326 US men and women ≥65 years of age and free of AF or heart failure at baseline, plasma phospholipid levels of eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid were measured at baseline by use of standardized methods. Incident AF (789 cases) was identified prospectively from hospital discharge records and study visit ECGs during 31 169 person-years of follow-up (1992-2006). In multivariable Cox models adjusted for other risk factors, the relative risk in the top versus lowest quartile of total n-3 PUFAs (eicosapentaenoic acid+docosapentaenoic acid+docosahexaenoic acid) levels was 0.71 (95% confidence interval, 0.57-0.89; P for trend=0.004) and of DHA levels was 0.77 (95% confidence interval, 0.62-0.96; P for trend=0.01). Eicosapentaenoic acid and docosapentaenoic acid levels were not significantly associated with incident AF. Evaluated nonparametrically, both total n-3 PUFAs and docosahexaenoic acid showed graded and linear inverse associations with incidence of AF. Adjustment for intervening events such as heart failure or myocardial infarction during follow-up did not appreciably alter results. CONCLUSIONS: In older adults, higher circulating total long-chain n-3 PUFA and docosahexaenoic acid levels were associated with lower risk of incident AF. These results highlight the need to evaluate whether increased dietary intake of these fatty acids could be effective for the primary prevention of AF.
Keywords: Aged; Atrial Fibrillation; Biomarkers; Dietary Fats; Docosahexaenoic Acids; Eicosapentaenoic Acid; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Incidence; Male; Proportional Hazards Models; Risk Factors; Seafood